2003
DOI: 10.1177/1420326x03012001019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Environment in Operating Theatres in Two Hospitals

Abstract: Hospitals and other health care facilities are complex environments that require specialised ventilation for the comfort of patients, personnel and visitors and to control hazardous emissions. Among the most highly specialised environments in hospitals are operating theatres. Health care personnel who work in surgical suites are potentially exposed to a number of airborne hazards and an environment that relies on ventilation to achieve a high air quality. We have tried to compare such environments in two very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…It is characteristic that the TVOCs concentration reduces after 12:00-12:30 LST, immediately after the termination of these operations. For the same reason, only one peak is observed (Figure 3) with mean value of 1200 µgr/m 3 . Detergent cleaning products in use during the break are also responsible for the enhancement of VOCs concentrations.…”
Section: Tvocsmentioning
confidence: 73%
See 1 more Smart Citation
“…It is characteristic that the TVOCs concentration reduces after 12:00-12:30 LST, immediately after the termination of these operations. For the same reason, only one peak is observed (Figure 3) with mean value of 1200 µgr/m 3 . Detergent cleaning products in use during the break are also responsible for the enhancement of VOCs concentrations.…”
Section: Tvocsmentioning
confidence: 73%
“…This issue becomes more complicated in hospitals located in urban areas, where additional pollution sources, including cars, industries, central heating can affect the indoor air quality status. Previous studies have demonstrated the formation of bad conditions in hospitals and have investigated possible sources (Loizidou et al [1], San-Jose-Alonso et al [2], Holcatova et al [3]). …”
Section: Introductionmentioning
confidence: 99%
“…A proper and a well-maintained air conditioning and mechanical ventilation system should provide a positive effect on reducing the concentration of anaesthetics gases and maintaining a desirable temperature in OR. 1 The surgical processes often require the application of gaseous anaesthetics for narcosis. Inevitably, the application of these gases to surgical procedure will cause a rise in concentration of narcotic gases within the surgeon’s working zone as well as delivering the anaesthetic to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The results of both measurement and simulation studies show that ventilation can improve indoor air quality. [5][6][7] Some research focuses on the optimal configuration or review of the ventilation system. The work of Santamouris and colleagues shows that the concentrations of CO 2 decrease with enhanced airflow rates.…”
Section: Introductionmentioning
confidence: 99%